Plans and specifications for a 500 drop telephone exchange - Thurston, Elbert Wren; Ferris, Arba C. (My University, 1906)
Introduction: In telephone systems as in all other different branches of business, the materials to be used should be of the best. This is advantageous to all the persons connected with the management of the system. The better the materials the better will be the service, and the less will be the future expenses to the owner. If a larger amount of money is invested at first, in buying the best materials, the amount will soon be made up in the better service, and the lowered expense of replacement. It is, then considered to be an advantage, to buy the best grade of materials, for use. It has been the purpose of the writers to determine what types of instruments, etc., will give the most satisfaction to the owner and subscriber of the average telephone exchange. Only such specifications have been given as are somewhat different from any of the present commercial forms. It is believed that if a system be planned embodying the special features here given, a most efficient system will be the result.
Citation: Thurston, Elbert Wren and Ferris, Arba C. Plans and specifications for a 500 drop telephone exchange. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Telephone Exchange; Telephone; Specificatfions; Blueprints; Equipment; Theses